Navigating cross-border institutional complexity: A review and assessment of multinational nonmarket strategy research - Sun, Pei; Doh, Jonathan P.; Rajwani, Tazeeb; Siegel, Donald (Journal of International Business Studies, 2021)
Multinational enterprises are deeply engaged in nonmarket strategy (NMS), including both corporate political activity (CPA) and strategic corporate social responsibility (SCSR). In this review, we document the multinational NMS research according to contributions' theme, method, context, theory, and level of analysis. We then develop an institutional multiplicity framework to organize our analysis of this large and fragmented body of literature. In so doing, we identify the most impactful contributions within three major themes - multinational CPA, multinational SCSR, and the integration of CPA and SCSR - and their respective subthemes, and call attention to limitations in the extant research. We also highlight promising avenues for future research, including expanding the scope of NMS to incorporate microfoundations research, integrating macrolevel scholarship on global institutions, placing greater attention on the interaction between CPA and SCSR, and incorporating multi-actor global issues and movements. Our review underscores the growing importance and missed opportunities of NMS research in the international business field.